French women's knowledge of and attitudes towards cervical cancer prevention and the acceptability of HPV vaccination among those with 14 - 18 year old daughters: a quantitative-qualitative study - Haesebaert Julie; Lutringer-Magnin Delphine; Kalecinski Julie; Barone Giovanna; Jacquard Anne-Carole; Régnier Véronique; Leocmach Yann; Vanhems Philippe; Chauvin Franck; Lasset Christine (BMC, 2012)
Abstract Background In France, it is recommended that girls and women aged 14-23 are vaccinated against the human papillomavirus (HPV). However, French women's knowledge of and attitude towards the vaccine has been little studied. Methods Thirty-nine general practitioners, representative of those working in the large Rhône-Alpes region, offered a self-administered questionnaire on cervical cancer (CC) prevention to all 18-65 year-old women who came for consultation during June and July 2008. In addition, semi-structured interviews were undertaken with a sample of those who had daughters aged 14-18. Results Of the 1,478 women who completed the questionnaire, only 16.9% mentioned HPV as the cause of CC, even though 76.2% knew of the vaccine. 210 women had daughters aged 14-18, and 32 were interviewed. Compared with the wider group, more of these women were aware of the HPV vaccine (91.4%). 44.8% knew the target population and 17.1% the recommended ages for vaccination. 54.3% favoured HPV vaccination; 37.2% were undecided and only 0.9% were opposed. The main barrier to acceptance was the recency of the vaccine's introduction and concern about possible side effects (54.9%); 14.1% preferred to rely on their GP's decision. Factors associated with acceptance of the HPV vaccine were having previously vaccinated a child against pneumococcus (OR=3.28 [1.32-8.11]) and knowing the target population for HPV vaccination (OR=2.12 [1.15-3.90]). Knowing the recommended frequency of Papanicolaou smear testing (Pap test) screening was associated with lower acceptance (OR=0.32 [0.13-0.82]). Conclusions Few mothers are opposed to HPV vaccination. Factors associated with acceptability were knowledge about the vaccine, acceptance of other vaccines and, unexpectedly, lack of knowledge about the recommended frequency of Pap testing. On multivariate analysis, compliance with recommendations for Pap test screening and socioeconomic factors had no effect on views about HPV vaccination. Given that concern about possible side effects is the major barrier to wider acceptance of the HPV vaccine in France, GPs have a key role in providing information.